Prevalence, Awareness, and Treatment of Hypertension in Patients with Type 1 Diabetes: A Nationwide Multicenter Study in Brazil - Gomes, Marilia B. (Hindawi Publishing Corporation, 2013)
Objective. This study evaluated the prevalence, awareness, and type of treatment for hypertension in Brazil in patients with type 1 diabetes (T1D). Methods. This was a cross-sectional, multicenter study that was conducted from December 2008 to December 2010 in 28 public clinics located in 20 Brazilian cities. Results. A total of 3,591 patients were studied, 56% female, average age 21.2 ± 11.7 years, with a median duration of diabetes 9.6 ± 8.1 years. Blood pressure levels were available for a total of 3,323 patients and 689 (19.2%) patients were hypertensive. Hypertensive patients were older, exhibited longer duration of diabetes, and had higher body mass index (BMI), total cholesterol, triglycerides, and LDL-C values (P < 0.001, for all comparisons), but only 370 (53.7%) received treatment. Patient awareness of hypertension was documented in 453 (65.5%) patients. However, only 76 (22.9%) of the treated patients attained the target systolic (sBP) and diastolic blood pressures (dBP). Conclusions. Our results demonstrate that a large number of T1D patients with hypertension do not receive appropriate treatment; few of the treated T1D patients achieved the target sBP and dBP values. Greater attention should be paid to blood pressure evaluation, hypertension diagnosis, and treatment of T1D patients in Brazil.